Guerrilla marketing attack : - Levinson, Jay Conrad (Houghton Mifflin, 1989)
One hundred weapons for the attack. The personality of the successful guerrilla. The seven-word winning credo -- From an art to a science -- Why launch an attack? -- Basic training for guerrillas -- A dozen tactics to consider -- Gaining effective media support -- Direct marketing, guerrilla style -- The most important person -- Thirty-three marketing myths -- Maintaining the attack--and the profits information arsenal for guerrillas.